PEMIKIRAN IMAM AL-GHAZALI DALAM PENDIDIKAN ISLAM - Mukromin Mukromin (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2019)
Al-Ghazali is a popular Muslim figure, with thoughts on education based on religion.Being able to realize education as a strategic tool and media in transforming religiousdoctrines. Al-Ghazali's thinking in the field of education places more emphasis onempiricism, this is because al-Ghazali attaches great importance to education of students.According to him, it depends on parents and people who educate him.